Gender Discrimination and Empowerment Issues Among HIV Positive Females Attending Anti-Retroviral Therapy Centre in Northern Karnataka - Venkatesha, Mahesh; Lakkappa, Lakshmi; Bant, Dattatreya D; Bathija, Geetha V (National Journal of Community Medicine, 2016)
Background: Since last decade a terrifying pattern has emerged in HIV and women face higher risks of being infected by HIV as well as increasingly bearing the brunt of its impact. Almost half of the adults living with HIV & AIDS today are women. Objectives: To determine socio-demographic profile, health status and gender, empowerment issues among HIV positive female patients. Methods: A cross sectional study was done among HIV positive women attending ART centre and linked to NGO’s. Pre-tested and pre-structured questionnaire was used to collect data. Proportions were estimated using SPSS statistics software version 22. Results: HIV infection was more common in women aged between 20-30 yrs, 59% of them were widow, 62% were literates and majority were in lower socio-economic group. Majority of women suffered from genitourinary infections. Family was non supportive in 28%, bad familial relation was seen in 34% of subjects. 22% faced Physical abuse, 61% were isolated in gatherings. Majority of women were not practicing any contraceptive measures. Conclusion: Literacy status and health education programmes of women must be increased to make them aware regarding contraceptives, health facilities, human rights, empowerment issues and to remove misconceptions of HIV.